2002
DOI: 10.1177/0957926502013002408
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapitalism: language, new media and social perceptions of value

Abstract: Using examples from contemporary policy and business discourses, and exemplary historical texts dealing with the notion of value, I put forward an argument as to why a critical scholarship that draws on media history, language analysis, philosophy and political economy is necessary to understand the dynamics of what is being called `the global knowledge economy'. I argue that the social changes associated with new modes of value determination are closely associated with new media forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
17

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 26 publications
0
42
0
17
Order By: Relevance
“…For the purposes of this paper we define political economy as the practical intersection of values (the economic) and power (the political) (Graham 2006). When one speaks of values and economics in the same sentence, the contemporary assumption is that the topic is money.…”
Section: Political Economy Values and Moral Philosophymentioning
confidence: 99%
“…For the purposes of this paper we define political economy as the practical intersection of values (the economic) and power (the political) (Graham 2006). When one speaks of values and economics in the same sentence, the contemporary assumption is that the topic is money.…”
Section: Political Economy Values and Moral Philosophymentioning
confidence: 99%
“…In response to our current, comparable situation, education systems in the "hypercapitalist" (Graham, 2005) economies of North America, Europe, and the AsiaPacific have attempted to respond to fundamental and profound changes in society, economy, and culture. Over the past three decades, they first viewed educational technology as a logical extension of school science and mathematics education; that is, as a matter of scientific technology and technique.…”
Section: What Is To Be Done?mentioning
confidence: 99%
“…These intersubjective cognitions are inseparable from the displays of information on the trading screens (see Knorr-Cetina and Bruegger, 2002). Trading transactions are themselves symbolic/communicative actions that reflexively constitute shifts in market reality by transforming the legitimate claims of ownership inscribed in the securities/assets traded and also by crystallizing intersubjectively recognized prices (see Graham, 2006;Thompson, 2003). Price movements are typically reported by media as external events attributable to the agency of 'the markets' as if they were an impersonal force of nature akin to the weather.…”
Section: Financial News and Informational Reflexivitymentioning
confidence: 99%
“…If enough investors pay attention to a source or a rumour then, at least in the short-term, financial news can generate self-fulfilling prophecies (Sant and Zaman, 1996). Davis's (2005) analysis of media effects on institutional traders in the London Stock Exchange suggested that while there was little evidence of direct effects in the manner assumed in early mass communication models, financial news was found to be influential in other ways: it provides indications of market consensus and what most market analysts are thinking, encourages traders to anticipate/preempt market reactions to expected media announcements, and cultivates an environment wherein real-time access to market information accentuates traders' sensitivity to what others in the market are doing thereby incentivizing herd-like behaviour (see also Graham, 2006;Thompson, 2003).…”
Section: Financial News and Informational Reflexivitymentioning
confidence: 99%